Cytotoxic T lymphocyte associated antigen-4 (CTLA4) expression with renal cell carcinoma subtype and staging - Sangundo, Muhammad Faham; Soerohardjo, Indrawarman; Heriyanto, Didik Setyo (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
In Indonesia, approximately 45% of renal cell carcinoma (RCC) patients are at an advanced stage that requires checkpoint inhibition combination immunotherapy. Cytotoxic T lymphocyte associated antigen-4 (CTLA-4) is associated with poor prognosis of RCC and it is the first checkpoint developed in cancer immunotherapy. This study aimed to investigate CTLA-4 expression among RCC subtypes and staging. Formalin fixed paraffin embedded (FFPE) tissue of RCC patients from 2018-2020 were obtained from the Department of Anatomical Pathology, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada/Dr. Sardjito General Hospital, Yogyakarta. Expression of CTLA-4 among RCC subtypes and stage was measured using quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and compared. Among the 40 patients involved in this study, the CTLA-4 expression was higher in papillary RCC/pRCC (95.88 + 31.58) compared to clear cell RCC/ccRCC (90.94 + 43.05). However, no significantly different in CTL-4 expression based on histologic subtypes and tumor stage (p>0.05). In conclusion, neither the histologic subtype nor the tumor stage of RCC can be predicted by CTLA-4 expression.